The plant hormone salicylic acid interacts with the mechanism of anti‐herbivory conferred by fungal endophytes in grasses. (9th January 2018) - Bastías, Daniel A.; Alejandra Martínez‐Ghersa, M.; Newman, Jonathan A.; Card, Stuart D.; Mace, Wade J.; Gundel, Pedro E.
Abstract: The plant hormone salicylic acid (SA) is recognized as an effective defence against biotrophic pathogens, but its role as regulator of beneficial plant symbionts has received little attention. We studied the relationship between the SA hormone and leaf fungal endophytes on herbivore defences in symbiotic grasses. We hypothesize that the SA exposure suppresses the endophyte reducing the fungal‐produced alkaloids. Because of the role that alkaloids play in anti‐herbivore defences, any reduction in their production should make host plants more susceptible to herbivores. Lolium multiflorum plants symbiotic and nonsymbiotic with the endophyte Epichloë occultans were exposed to SA followed by a challenge with the aphid Rhopalosiphum padi . We measured the level of plant resistance to aphids, and the defences conferred by endophytes and host plants. Symbiotic plants had lower concentrations of SA than did the nonsymbiotic counterparts. Consistent with our prediction, the hormonal treatment reduced the concentration of loline alkaloids (i.e., N‐formyllolines and N‐acetylnorlolines) and consequently decreased the endophyte‐conferred resistance against aphids. Our study highlights the importance of the interaction between the plant immune system and endophytes for the stability of the defensive mutualism. Our results indicate that the SA plays a critical role in regulating the endophyte‐conferred resistance against herbivores. Abstract : Our understanding of the impacts of plant defences on certain beneficial microorganisms has increased rapidly. Nevertheless, virtually nothing is known about the impacts of plant immune responses on symbiotic fungal endophytes. Our study represents a first attempt to elucidate the mechanisms regulating this interaction. Specifically, our results indicate that the hormone salicylic acid plays a critical role in regulating the endophyte‐conferred resistance against insect attackers. Thus, this study helps to elucidate the functional bases of the resistance responses of plants in symbiosis with leaf fungal endophytes.